Heart fat in HIV: marker or mediator of risk?. Issue 6 (November 2017) - Buggey, Jonathan; Longenecker, Chris T.
Abstract : Purpose of review: The review aims to summarize the literature describing the clinical impact of cardiac fat depots in patients with HIV infection. Recent findings: People living with HIV (PLHIV) have accelerated rates of cardiovascular disease, and are prone to the development of ectopic fat deposition. Specifically, PLHIV have higher volumes of epicardial and intracardiac fat quantified by noninvasive imaging. Higher volumes of epicardial fat may be related to antiretroviral therapy duration and chronic inflammation, independently of other measures of body adiposity such as BMI. They have been associated with increased coronary artery calcium, myocardial perfusion defects, death, and myocardial infarction. The association with risk may be partly mediated through direct actions of cytokines and adipokines produced by the adipose tissue. Furthermore, HIV-infected patients have increased myocardial fat deposition that is also associated with antiretroviral therapy duration, and may be responsible for myocardial systolic and diastolic dysfunction. Summary: PLHIV have increased fat deposition surrounding and inside the heart that may serve as an important imaging marker of risk but may also directly mediate coronary artery disease and cardiac dysfunction. Although robust data of targeted therapies is lacking, some pharmacotherapies may be able to reduce cardiac fat volumes. In the meantime, as the evidence grows, physicians may consider intensifying preventive strategies and monitoring in patients with abnormal heart fat on noninvasive imaging.